The Contribution of Social Entrepreneurship to the Development of Human Capital of Students - Klushina, Nadezhda P.; Roshchupkina, Violetta V.; Kotov, Sergey V.; Petrova, Nina P.; Abdulgalimov, Ramazan M. (International Journal of Criminology and Sociology, 2022)
The article presents the author’s vision of the place and role of social entrepreneurship in the development of the human capital of students. The authors note that the ongoing changes in society and the economy pose the most important task - the study of a phenomenon such as human capital. Training in social entrepreneurship of students can somehow contribute to the formation of the individual human capital of a student to more successfully adapt to the modern labor market. The authors proposed a model of human capital consisting of seven components, which served as the basis for the development and implementation of a modular curriculum in the work of several universities. The article presents a pedagogical experiment on testing a modular program at universities in the South and North Caucasus Federal Districts and evaluates its results. Suggestions were made for the development of an urgent and state-important strategic direction for universities - a focus on the formation of positive human capital for students.